Perancangan Bangunan Mixed-Use di Pasar Minggu Jakarta Selatan - Nurjam’an Nurjam’an (Fakultas Teknik - Universitas Bung Karno, 2023)
This research is about how to design market and residential mixed-use buildings that are integrated with the environment and transportation facilities in Pasar Minggu. The purpose of the design is to realize an efficient building as a place to live and work that can utilize the potential of the environment. The location chosen as the site of the design object is the Pasar Minggu area as one of the strategic transportation facilities in Jakarta. In preparing the design concept, the following problems were proposed: (1) How to integrate market and residential functions in the Mixed-Use concept, (2) How to develop an integrated design with an environment that accommodates the needs and principles of T.O.D-based area design (Transit Oriented Development). This research uses analytical descriptive research methods by collecting data through literature studies, surveys and documentation as well as interviews. From the results of the discussion, it can be stated that the implementation of shared facility design, market layout arrangement, and accessibility through the development of vertical space based on zones, connecting spaces and shared spaces.